2000
DOI: 10.1002/etc.5620190118
|View full text |Cite
|
Sign up to set email alerts
|

Using single‐species toxicity tests, community‐level responses, and toxicity identification evaluations to investigate effluent impacts

Abstract: Abstract-Whole effluent toxicity (WET) tests are increasingly used to monitor compliance of consented discharges, but few studies have related toxicity measured using WET tests to receiving water impacts. Here we adopt a four-stage procedure to investigate the toxicity and biological impact of a point source discharge and to identify the major toxicants. In stage 1, standard WET tests were employed to determine the toxicity of the effluent. This was then followed by an assessment of receiving water toxicity us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 23 publications
(26 reference statements)
0
34
0
Order By: Relevance
“…Amphipods, remaining leaf discs and any leaf tissue shredded off were removed after seven days of exposure, dried and weighed as described above. The feeding rate observed during the in situ bioassays as well as the laboratory feeding trial was calculated in milligram of consumed leaf mass per milligram dry weight of Gammarus per day (Maltby et al, 2000).…”
Section: In Situ Bioassays and Laboratory Feeding Trialmentioning
confidence: 99%
“…Amphipods, remaining leaf discs and any leaf tissue shredded off were removed after seven days of exposure, dried and weighed as described above. The feeding rate observed during the in situ bioassays as well as the laboratory feeding trial was calculated in milligram of consumed leaf mass per milligram dry weight of Gammarus per day (Maltby et al, 2000).…”
Section: In Situ Bioassays and Laboratory Feeding Trialmentioning
confidence: 99%
“…The daily detrital processing rate measured during the first experiment was expressed as milligram of leaf mass loss per milligram dry mass of amphipod, while only replicates without mortality were assessed (Maltby et al 2000). To gage statistically significant differences between treatments, CI testing as described by Altman et al (2000) and suggested by Cumming (2012) was employed for detrital processing and bioaccumulation data for each contact time.…”
Section: Discussionmentioning
confidence: 99%
“…Amphipods, remaining leaf discs and any leaf tissue shredded off were removed after seven days of exposure, dried and weighed as described above. The feeding rate was calculated in milligram per milligram dry weight of Gammarus per day [28].…”
Section: Feeding Trialmentioning
confidence: 99%